Trije Kafkovski romaneskni svetovi - Kepic Mohar, Alenka (Jezik in slovstvo, 2000)
A comparison of three contemporary Slovene novels - Galjot by Drago Jančar, Raza by Feri Lainšček and Stari pil by Vlado Žabot - with Kafka's novels The Trial and the Castle and his story Metamorphosis reveals interesting parallels, but also some departures in the depiction of the main characters inthe Slovene texts, which are a continuation of certain enduring characteristic of the Slovene novel.
Keywords: Jančar, Drago, 1948-; Lainšček, Feri, 1959-; Žabot, Vlado, 1958-; Kafka, Franz, 1883-1924; Slovene literature; slovenska književnost; German-language literature; nemška književnost; literarne študije; primerjalna književnost; comparative literature